Investigation into the mechanisms of gas sensing using carbon nanotube electronic devices - Fam, Derrick Wen Hui (2012)
Carbon Nanotubes (CNTs) are one of the advanced functional materials now widely researched for their gas sensing properties due to their exceptional inherent attributes. However, due to the lack of understanding of the controlled synthesis and deposition of CNTs in making consistent devices and the sensing mechanisms involved, commercialization is still elusive. Furthermore, there are still controversies to whether the sensing occurs via electrode-CNT junction effect or channel effect. These studies were further complicated by the fact that the CNTs used were a mixture of semiconducting and metallic nanotubes. Therefore, to begin to arrest these issues, a novel method of Electrostatic Atomization was developed for the deposition of CNTs to make transistor sensors with improved gate control in this work. Following which, to study the mechanisms of sensing, three different approaches were embarked on. Firstly, the CNT channel alignment effects were compared and it was found that channel alignment contributes to the sensitivity of the CNT. However in comparison with transistor devices, it was found that even though sensing was improved by channel alignment, electrode-CNT junction effects still played a predominant role. Since the CNTs used were a mixture of semiconducting and metallic ones, therefore in the second study, pure nanotubes were used. It was discovered that the sensing mechanisms of semiconducting tubes were much different from that of metallic tubes with the former showing more sensitivity. However, even though through the two studies, it was established that junction effects contributed to most of the sensitivity of pristine CNTs, it was discovered in the third study that decorations along the length of the CNT increases its sensitivity and imbues selectivity as well.